MENCEGAH PENYAKIT PARKINSON KEPADA GURU PENDIDIK SEKOLAH DASAR YANG BERUSIA DI ATAS 50 TAHUN - Hutajulu, Maria Margareta (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
Abstract: Parkinson's disease is a neurodegenerative disorder commonly affecting older individuals, including elementary school teachers aged 50 and above. This study aims to address the problem of elementary teachers' vulnerability to Parkinson's disease at age 50 and explore preventive solutions. Risk factors such as occupational stress, environmental exposure, and lifestyle were examined to understand their role in developing Parkinson’s in teachers. Recommendations include adopting a healthy lifestyle, effective stress management, and routine health check-ups to reduce risk. This research aims to provide preventive insights beneficial for teachers.Keywords: Disease, Parkinson's, Teacher Educator, Elementary School, 50 Years.